2016
DOI: 10.1002/admi.201600806
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Conductivity of Polyaniline through Doping by Means of Single Precursor Vapor Phase Infiltration

Abstract: This work describes a novel single precursor vapor phase infiltration (VPI) process to dope polyaniline (PANI). The infiltration is performed with the metal containing atomic layer deposition precursors MoCl5 or SnCl4. The conductivities are assessed with four‐point probe measurements and show significant enhancements by up to 6 orders of magnitude, confirming the efficiency of the VPI process. Furthermore, it is found that the conductivities of PANI/MoCl5 and PANI/SnCl4 outperform the conductivity of HCl‐dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 32 publications
5
49
1
Order By: Relevance
“…These final hybrid materials are intermixed organicinorganic hybrid structures with properties distinctly different from the original polymer. 11,12 For example, VPI has been used to increase the toughness of spider silk, 13 increase the electrical conductivity of semiconducting polymers, 14 and increase the solvent stability and separation performance of membranes. 15 A recent investigation examined the use of vapor phase infiltration to incorporate inorganic materials into block co-polymers containing a rubber (elastomeric) block.…”
Section: Introductionmentioning
confidence: 99%
“…These final hybrid materials are intermixed organicinorganic hybrid structures with properties distinctly different from the original polymer. 11,12 For example, VPI has been used to increase the toughness of spider silk, 13 increase the electrical conductivity of semiconducting polymers, 14 and increase the solvent stability and separation performance of membranes. 15 A recent investigation examined the use of vapor phase infiltration to incorporate inorganic materials into block co-polymers containing a rubber (elastomeric) block.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the crystallinity and decrease in PANI nanorods size upon the inclusion of SLS might have contributed in enhancing electrical conductivity. Overall, SLS effectively acted as a protonation agent, which leads to an increase in the electrical properties of PANI by forming an anilium/SLS compound [29,[58][59][60].…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Besides depending on different oxidation states of the polymer (fully reduced leucoemeraldine, half oxidized emeraldine base and fully oxidized pernigraniline states) [ 98 ], the PANI conductivity can be modified through SIS doping. In 2017, Wang et al [ 99 ] reported doping of PANI with metal chlorides by considering and precursors. In particular, it was observed that the conductivity of the infiltrated polymer (measured by means of four-probe techniques to avoid the effect of contact resistances) is correlated to the number of infiltration cycles and can be enhanced by up to six orders of magnitude.…”
Section: Control Of the Materials’ Functional Properties By Sismentioning
confidence: 99%